(untitled) (Research, Society and Development, 2020)
Average tests and correlation analysis (simple, canonical and trail) allow the identification of characters correlated with grain yield. Due to the low availability of studies that report the levels of correlation between soybean plants and the spacing between rows and the demands of rural producers, the aim of this study was to identify the influence of the spacing between rows of soybean genotypes on yield levels. , through statistical methodologies of averaging test, regressions and correlations. The study was conducted under field conditions at Fazenda Quero-Quero, in the municipality of Chapadão do Céu, Goiás, Brazil. The experimental design was a randomized block with 8 treatments, corresponding to 2 soybean genotypes (Desafio and M7739), submitted to 4 spacing between lines (22.5, 45, 67.5 and 90 cm) in 4 repetitions. Eight characters were quantified to explain grain yield. The analyzes were performed using the R Core Team statistical program. The characters showed interaction between the sources of variation and significance for the main effects. Correlations were described in the canonical variables and their direct and indirect effects were measured. At the end of the work, it was concluded that the line spacing and the genetic factor alter the soybean crop yield averages, and that the yield of the challenge and M7739 soybean genotypes is correlated with the stand, plant height and vegetables with two grains.